Study on the Development and Performance of a Wide-range Quadrupole Mass Spectrometer - FENG Tian-you;CHENG Yong-jun;CHEN Lian;DONG Meng;WANG Xing-hui;GUO Wen;RONG Zhen-hua;SUN Wen-jun (Zhipu Xuebao, 2023)
Monitoring of gas composition in long term manned confined spaces such as space stations and submarines has raised the requirement for a wide mass range quadrupole mass spectrometer. In the present work, according to the ion motion trajectory in the alternating electric field and electrostatic field, the physical parameters and structure dimensions of the ion source, mass analyzer and ion detector were designed, and a wide-range quadrupole mass spectrometer was developed at the Lanzhou Institute of Physics. The weight of its physical unit is 2.05 kg, its dimensions are approximately (315×145×60) mm3, and the power consumption is 86 W. The key performance indexes of the instrument were tested, and the results showed that the mass spectrometer can record mass range from 2 u to 614 u, and that the Faraday and multiplier detection sensitivity were 2.62×10-6, and 13 A/Pa for argon, respectively. According to the calculation of RF power supply voltage, the upper limit of mass number can reach 1 048 u, but no reference material testing was conducted. The mass resolution of the spectrometer at full width half maximum (FWHM) are 0.95 u (m/z 2)、0.72 u (m/z 40)、0.78 u (m/z 132) and 1.32 u (m/z 614) in different mass segments. It was shown that the resolution of the instrument is similar in the middle mass range, but poor in small mass range and high mass range. The reason for the poor resolution at m/z 2 is that the ion mass to charge ratio is small, the axial velocity is high, so the ions have left the quadrupole field before being fully separated. There are two reasons for the poor resolution at m/z 614. One is that the ion mass charge ratio is large and the axial speed is small, which is greatly affected by the edge field at the entrance edge of the quadrupole mass analyzer. The other is that the stability becomes worse when the RF power supply outputs high voltage. These factors will lead to the poor resolution in the large mass range. The upper limit of linear working pressure is nearly 1.39×10-3 Pa, the instrument signal strength stability is about 2.6% within 4 h, and the stability of the mass axis is ±0.1 u within 8 h. Finally, the instrument was compared with QMG700 quadrupole mass spectrometer. We found that our spectrometer had similar mass range, sensitivity and working pressure, but worse partial pressure ratio and stability, requiring improvement in its electrometer and RF power supply. We anticipate that this wide-range quadrupole mass spectrometer after improved could be used in space exploration, military technology, food safety and so on.